Proposta de Framework para a convivência entre Métodos Ágeis e o processo orçamentário nas organizações - Cravo, Lucas Terra (2024)
With the growing adoption of management practices aligned with Agile methodology, there is a need for organizations to adapt their internal processes for planning and projecting outcomes. This study investigates the conflicts and adaptations in budgetary processes arising from the implementation of Agile methods. The theoretical framework explores studies assessing the integration of agile methods in the financial planning of companies, addressing the conflicts that arise with existing processes, the adaptations made, and the critical factors essential for the success of this integration. Utilizing the Design Science Research methodology, the primary goal is to propose a framework that facilitates the coexistence of Agile methods and budgetary processes in organizations. Expert interviews were conducted and two rounds of validation of the proposed framework were applied. The main contributions include the identification of conflicts, critical factors for change, and the proposal of practical solutions for the harmonious integration of these methods. The findings challenge predefined financial planning models, highlighting the necessity for a customized approach for each organization. The results suggest that flexibility and decentralization are crucial for successful adoption of Agile methods in the budgetary context, while also emphasizing the importance of critical factors such as organizational culture, knowledge, and leadership commitment. This study provides a comprehensive view on the adaptation of budgetary processes in Agile environments, contributing to both theory and managerial practice.